Kajian Kontrastif Fonologi Bahasa Jawa Dialek Wonosobo dengan Dialek Solo-Yogyakarta (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
This article aims to examine the variations in Javanese speech by Javanese dialect speakers in Garung District, Wonosobo Regency, Central Java. The author uses phonological and phonemic process studies to identify the speech data of Javanese speakers. In the data collection process, the author uses the techniques of listening, recording, and tapping. The qualitative descriptive method is applied to describe the results of the study. In identifying variations of Javanese vowels and consonants speech in the Wonosobo Regency, the author uses a contrastive method with the standard Javanese Solo-Yogyakarta dialect. The study results show that there are several variations of Javanese speech by Javanese speakers in Garung District, Wonosobo. These variation utterances include changes in the vowel sound [ͻ] to [a], the vowel sound [e] to [a], the vowel sound [a] and [ɛ] to [e], the vowel sound [u] and [ᴐ] to [ o], and the consonant [y] changes to a fricative consonant [z]. Furthermore, based on the identification of phonemic processes, there are additions of sounds called paragoge and prosthesis, phonemes reduction of apheresis, and substitution of vowel sounds in words that have affixation. The study results can be used as material for further studies related to linguistic studies of Javanese dialects in Wonosobo, especially concerning lexicon and syntax aspects as well as socio dialectological maps of Javanese dialects in Wonosobo. Keywords: Javanese Wonosobo dialect, contrastive phonology, language variation, phonemic processes